Reliability Modeling of Wireless Sensor Network for Oil and Gas Pipelines Monitoring - Khalid EL-DARYMLI (Sensors & Transducers, 2009)
Extensive network of pipelines carrying oil and gas is an integral part of any country’s energy management plan. As oil and gas are characterized as highly hazardous, their transportation through pipelines warrants proactive continuous monitoring. Unfortunately, there has been limited continuous monitoring of this crucial infrastructure, which causes financial losses to the industry. This paper presents a wireless sensor network (WSN) system and its reliability assessment model for oil and gas pipelines condition monitoring.